Effects of Reproductive Health Education Using Video Animation Towards Reproductive Health Knowledge and Attitudes in 5th and 6th Elementary Grade Students in Serang City, Banten - Edy Mustofa; I Made Arya Subadiyasa; Agus Sholahuddin; Arif Rahman Nurdianto (Universitas Wijaya Kusuma Surabaya, 2021)
Introduction: Adolescent reproductive health education aims to increase knowledge and attitudes about reproductive health. Therefore, an easy, inexpensive, and standardized method of education is needed in the delivery of reproductive health material to young adolescents, one of them is audiovisual media animationMethod: The research was conducted using a pre-experimental research design pretest-posttest one group design within 31 days. This study used a total sample of 180 subjects, furthermore, the data were analyzed using Structural Equation Modeling (SEM).Result: Education with reproductive health animated videos increased knowledge about reproductive health immediately after education was given (P = 0.002), but after 31 days, it did not affect (P = 0.171). Education with animated videos did not affect the subjects’ attitude immediately after education was carried out (P = 0.802) but had an effect after 31 days from the start of education (P = 0.031). After analyzing the correlation including other confounding variables (R square), it was found that the effect of education with animated videos towards the increasing knowledge of reproductive health was 14.9%, and 8.4% towards changes in subject attitudes.Discussion: Health education with video animation increases knowledge, but the phenomenon of attitudes such as dating still occurs even the subjects’ knowledge have increased.Conclusion: Reproductive health education using animated videos increases knowledge but does not change attitudes in reproductive health